PSYCHOPATHOLOGICAL PROBLEMS IN A BOYS AND GIRLS CLINIC SAMPLE: EMPIRICAL TAXONOMY - López Soler, Concepción; García Montalvo, Carmen; Murcia, Laura; Martín, Carlota; Cortegano, Carmen; López-Mora, Isabel; López-García, Genoveva (Anales de Psicología / Annals of Psychology)
The objetive of this investigation is knowing psychopathologic symptoms gathering in a boys and girls with clinic problems sample. This objetive is carried forward working with a global sample of child's clinic population, which is divided en two subsamples, one of boys and one of girls.From methodological point of view, the symptoms and their gravity have been assessed through a behavior assessment checklist; the facts obtained with this instrument were statistically analyzed through multivariate analysis methods (factorial). The empirical gatherings obtained, that is to say the analysis results achieved have been compared with the internalizing and externalizing ample spectrum syndromes, which have been described among others by Achenbach and Edelbrok, and the restricted spectrum syndromes as anxiety, depression, hiperactivity, aggressiveness, etc. In this way, the child's hierarchical structure, alow us to know, besides of the empirical syndromes, the participation of certain symptoms in several psychopathologic squares.